World-Wide Web-Based Graphical User Interfaces for Laboratory Data - Keller, D.; Schaller, W. J.; Wong, J. S. K.; de Groen, P. C. (Methods of Information in Medicine, 2002)
Objectives: Electronic medical record systems permit collection of large amounts of medical information. Usually, information is presented in a fixed format, either as text or tables. Health care providers have to navigate this fixed format in order to find information useful for a specific patient-provider interaction. The main objective of this work was to allow the provider immediate access to specific laboratory information through the development of a highly customizable, graphical user interface to the Mayo Clinic laboratory information system.Methods – Results: Here we describe this platform-independent, World-Wide-Web-based graphical user interface that allows the provider to see all or a predetermined panel of essential laboratory data in graphical format. Advantages include availability at internet-based workstations, immediate recognition of trends over time, ability to zoom in and out of specific periods of time, and detailed analysis of patient values in relationship to normal values.Conclusions: Web browser-based user interface allowing graphical display of laboratory data using Java technology was described. The connection to the Mayo Clinic laboratory information system combines cross-platform support for use on virtually any networked machine, interaction through a Web browser for ease of use, and a combination of the Perl and Java languages for powerful data processing and interactivity.
Keywords: WWW; graphical user interfaces; laboratory data; medical database